THE ROLE OF COMPETENCIES, FINANCIAL PLANNING, AND ACCESS TO FINANCE IN EXPLAINING SMEs FINANCIAL INNOVATION - Hadi Ismanto; Tantri Pratiwi; Nurin Zulianti; Akhmad Abdul Qofur (Jurnal Manajemen dan Kewirausahaan, 2022)
Finance was a crucial aspect for the survival of SMEs. This study explored the factors that can influence financial innovation. Data was collected from the results of distributing questionnaires to 285 SMEs using a door-to-door approach and filling assistance. Sampling was based on the proportion of small and medium-sized industries. The data were tested with a series of statistical tests to obtain a suitable regression result. These results indicated that financial innovation was influenced by the owner or manager's entrepreneurial competence. Meanwhile, access to finance and financial planning did not affect financial innovation. Additional funds from outside the company were deemed necessary when the owner or manager of SMEs applies their maximum competence for business growth and performance. Therefore, it forced SMEs to be smart in exploring financial sources. SMEs tent to use their finance access to finance their business operations rather than making financial innovations. SMEs did not think about exploring their finances anymore because they feelt they had enough loans obtained from one institution. Even though the knowledge of SME owner or manager financial planning was quite good; they prefered not to make financial planning and let the cash flow normally.